Inequality Causes and Consequences. - Lorenzo Cappellari; Solomon W Polachek; Konstantinos Tatsiramos (Research in Labor Economics,, 2016)
Inequality has been rising in many countries over the last decades and the process seems to have accelerated with the Great Recession. Not only is income distribution more unequal today than 40 years ago, but also its transmission through generations has increased. In other words, many countries no longer experience upward economic mobility as was prevalent in the past. Research in Labor Economics volume 43 contains new and innovative research on the causes and consequences of inequality. Topics include the way inequality is measured, the level of equal opportunities across countries, the impact of education, the effect of changing occupational structure, the consequences of changing productivity within the firm, the roles of stagnating average real wages, the decline of union membership, the effect of maternal labor supply on labor market outcomes of their children, and the link between income inequality and health.